A theoretical framework for the awareness of phishing attack / Aida Rozihan Mohamad Asri and Irni Eliana Khairuddin - Mohamad Asri, Aida Rozihan; Khairuddin, Irni Eliana (Faculty of Information Management, 2022)
The increasing of internet usage as well as rapid technology evolves has caused the growing number of people who commit to cybercrime. Phishing is a type of cyber-attack in which an attacker sends a message to a targeted individual or organization with the intent of stealing personal information that phishers can use against them. Since phishing attacks are being developed and rising every year, internet users need to educate themselves and gain some knowledge about phishing attacks. The objective of this paper is to discuss the awareness of people towards phishing attack